Childhood-onset systemic lupus erythematosus: characteristics and the prospect of glucocorticoid pulse therapy - Pan, Lu; Liu, Jinxiang; Liu, Congcong; Guo, Lishuang; Punaro, Marilynn; Yang, Sirui (Frontiers in Immunology, 2023)
Childhood-onset systemic lupus erythematosus (cSLE) is an autoimmune disease that results in significant damage and often needs more aggressive treatment. Compared to adult-onset SLE, cSLE has a stronger genetic background and more prevalent elevated type I Interferon expression. The management of cSLE is more challenging because the disease itself and treatment can affect physical, psychological and emotional growth and development. High dose oral glucocorticoid (GC) has become the rule for treating moderate to severe cSLE activity. However, GC-related side effects and potential toxicities are problems that cannot be ignored. Recent studies have suggested that GC pulse therapy can achieve disease remission rapidly and reduce GC-related side effects with a reduction in oral prednisone doses. This article reviews characteristics, including pathogenesis and manifestations of cSLE, and summarized the existing evidence on GC therapy, especially on GC pulse therapy in cSLE, followed by our proposal for GC therapy according to the clinical effects and pathogenesis.